Physiological response of the white yam (Dioscorea rotundata Poir) to planting densities - Pérez, Dairo J.; Campo, Rodrigo O.; Jarma O., Alfredo (Revista de Ciencias Agrícolas, 2015)
This research aimed to study the physiological response of the white yam (Dioscorea rotundata cv. brasilero) in relation to increasing planting densities under environmental conditions of the mid-Sinú region. This study was conducted at the Universidad de Córdoba (Montería, Colombia), there four planting densities: f 45.455, 30.303, 22.727, and 10.101 plants/ha were evaluated through a randomized complete block design with three repetitions. The response variables assessed were net photosynthesis (Pn) -measured in three phenological stages (vegetative, start and end of tuberization)- and growth indices, such as absolute growth rate (AGR), net assimilation rate (NAR), relative growth rate (RGR), and leaf area index (LAI). The Pn did not vary between planting densities (p≤0.05), but was reduced in average by 19.14% after the vegetative stage, for the start and end of tuberization. The AGR and RGR showed a similar tendency, with an increase in the vegetative stage, but a reduction towards the end of the cycle. The NAR began to increase in the vegetative stage, with a slight increase at the end of the cycle. The LAI increased significantly in tuberization for planting densities above 10.101 plants/ha, reaching values between 3.08 and 4.03. It is concluded that the growth indices evaluated, except for LAI and Pn, did not vary between planting densities, likely due to the species’ capacity to regulate its physiological activity in relation to the planting density.